Compositional Constraints of Ice Lobes at the Edge of Martian South Polar Cap and the Possibility for CO2 Ice - Xu Meng; Yi Xu; Qi Jin; Long Xiao; Xiaoting Xu; Hai Liu (The Astronomical Journal, 2023)
As one of the major ice reservoirs on Mars, the south polar layered deposits (SPLD) are mainly composed of water ice and dust except for the perennial CO _2 ice deposits on the surface and within buried layers. At the edge of Planum Australe, the Shallow Radar detected the base of two ice lobes, which can be used to estimate their dielectric properties and analyze the components. These measurements, combined with topographic data, allow for the relative permittivity of the lobe materials to be estimated at 2.73 ± 0.67. Under the constraint of the SPLD density, the permittivity value translates to the existence of CO _2 ice depending on the dust content. If the dust content is larger than 24%, the lobes are CO _2 free and composed of water ice, dust, and pore space. Whereas, for the dust content of <12%, our results suggest that the lobes must contain a certain amount of CO _2 ice, which could be an average volume of 30%. When the dust content is between 12% and 24%, the existence of CO _2 ice is undetermined. This study improves the understanding of ice deposits at the Martian south polar.